2007
DOI: 10.1590/s1413-81232007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Saber popular sobre dores nas costas em mulheres nordestinas

Abstract: Analyzing and understanding people's conceptions and actions regarding back pain is relevant since they can be part of the disease's explanation and cure. The nature of this study is qualitative with an anthropological focus. It was carried out from January to February, 2005 with nine women between 45 and 58 years of age with chronic back pains who participated in a health support group for menopausal women in a teaching institution in Fortaleza, Ceará. Nine (9) in-depth ethnographic interviews were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
1
12
0
3
Order By: Relevance
“…The PT1 participants reported no understanding or partial understanding of the instructions and items 1,2,4,6,7,9,11,12,15,17,27,32,34,39,40,42,43,47,50,56 and 63, totaling 21 items. The item 7 "I was able to do more, just going a little slower and giving myself occasional breaks" which was pointed out as "not understood" by all the participants.…”
Section: Pre-test -Pt1mentioning
confidence: 99%
See 2 more Smart Citations
“…The PT1 participants reported no understanding or partial understanding of the instructions and items 1,2,4,6,7,9,11,12,15,17,27,32,34,39,40,42,43,47,50,56 and 63, totaling 21 items. The item 7 "I was able to do more, just going a little slower and giving myself occasional breaks" which was pointed out as "not understood" by all the participants.…”
Section: Pre-test -Pt1mentioning
confidence: 99%
“…The search for Brazilian studies on the topic identified only 8 original studies that addressed issues related to coping with CP, and that discussed the CS pointed out by the participants. In total there were three master's dissertations [34][35][36] , one doctoral thesis 7 and four articles [37][38][39][40] , besides two book chapters 41,42 . The studies pointed out important contents concerning CS for pain among Brazilians that are not addressed in the CPCI, such as the search for pharmacological treatment and complementary therapies, in addition to religious practices and spirituality.…”
Section: Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a dor torna-se crônica e passa a limitar a qualidade de vida e as condições de trabalho (ARCANJO; SILVA; NATIONS, 2007).…”
Section: Gráfico 4 -Distribuição Das Manicures E Pedicures Quanto à Aunclassified
“…O "catarro" e o "cansaço" causam o medo da morte iminente, a vergonha por estar em ambiente público e o mal-estar, muitas vezes incontrolável, sentimentos presentes em outros processos crônicos que traduzem sinais e significados que sufocam as pessoas 12,21,27,40,41 , amedrontando os doentes 42 e determinando mudanças pessoais e familiares. Porém, pior do que estar preso com o "catarro" é sentir-se numa crise inesperada, às vezes de difícil controle, tendo como causa um problema de família, a própria doença ou outros aspectos emocionais também observados na asma, enfermidade com características semelhantes à doença pulmonar obstrutiva crônica 43 .…”
Section: Sopro De Vida: Superar Os Danos Da Doença Pulmonar Obstrutivunclassified